Fetal Thoracic Malformation at 13 weeks of Gestation Associated With Turner Syndrome: A Case Report - Dündar, Özgür; Müngen, Ercüment; Çalışkan, Ahmet Cantuğ; Muhcu, Murat; Atay, Vedat; Yergök, Yusuf Ziya (Gynecology Obstetrics & Reproductive Medicine, 2007)
In the present case report, we stated the intercourse between thoracic vascular malformations observed in the first trimester of pregnancy and Turner syndrome. Prenatal doppler findings of the vascular tumor and its relation with Turner syndrome is also evaluated. Since the introduction of antenatal screening programs for Turner syndrome based on nuchal translucency thickness in the first trimester of pregnancy, increasing number of fetal structural abnormalities are being detected at the 11-14 week ultrasound scan. Furthermore, cardiovascular complications are the main cause of increased mortality in Turner syndrome.